Discovery of the large-scale thrust nappe and its geological significance in the southwestern Santanghu fold–thrust belt, NW China - Zhen, Yu; Xu, Xiongfei; He, Dengfa; Li, Xinning; Li, Di (Frontiers in Earth Science, 2023)
Studying structural evolution of the piedmont fold and thrust belt is one of the most important methods to interpret the mechanism of intracontinental collision orogeny. In this study, we have discovered a long-distance large-scale thrust nappe with a width of about 20 km in the southwestern margin of the Santanghu Basin, which provide a good evidence for studying the Mesozoic-Cenozoic tectonic evolution mechanism of the Moqinwula Mountain. Using the electromagnetic profile and high resolution seismic profile, we have determined that the hanging wall of the nappe is composed of the pre-growth strata of Carboniferous-Middle Jurassic and the syntectonic strata of Cretaceous-Quaternary. The nappe is subjected to two branch faults of the Baiyishan thrust, forming a breakthrough fault propagation fold and a fault bend fold along the detachment layer of the Haerjiawu Formation, and a large monoclinic structure is formed by the basement structural wedge near the mountain root. The growth strata and unconformity structure record that the fold-thrust belt have experienced five episodes thrusting from Late Triassic to Quaternary. Based on sequential restoration and forward modeling, we propose that the southwestern margin of the Santanghu Basin has been shortened by at least 55 km, mainly in the Late Jurassic and Late Cretaceous. Our results provide an excellent example for studying the mechanism of the transition from Yanshanian compression-torsional to Himalayan thrust compression in the Eastern Tianshan region.